A study of body composition and its association with disease severity in stable chronic obstructive pulmonary disease patients in HUSM - Asmee, Mohammad Faisal (2011)
Background: COPD is not just a disease of the lungs alone; it has systemic manifestations due to the underlying pathogenesis of inflammatory reaction. Systemic manifestations in term of reduction in body composition (Body Mass Index and Fat Free Mass Index) has been shown to be an independent risk factor for disease severity and mortality in COPD. The objective of this study is to determine the association of body composition with disease severity in stable COPD patients (patients who had no exacerbation in the past three months). Methods: We evaluated 38 stable COPD patients attending Respiratory Clinic in HUSM and calculated their Body Mass Index, Fat Free Mass Index and determined their six minutes walking distance and serum CRP values. Results: There was no satisfactory significant difference between body composition and disease severity in COPD patients noted in this study ( p > 0.05 ). Conclusion: Body composition (BMI,FFMI) is not suitable for assessment of disease severity in stable COPD patients.